Evaluation of the immunomodulatory effects of interleukin-10 on peripheral blood immune cells of COVID-19 patients: Implication for COVID-19 therapy - Najafi-Fard, Saeid; Petruccioli, Elisa; Farroni, Chiara; Petrone, Linda; Vanini, Valentina; Cuzzi, Gilda; Salmi, Andrea; Altera, Anna Maria Gerarda; Navarra, Assunta; Alonzi, Tonino; Nicastri, Emanuele; Palmieri, Fabrizio; et al. (Frontiers in Immunology, 2022)
Objective: Several therapies with immune-modulatory functions have been proposed to reduce the overwhelmed inflammation associated with COVID-19. Here we investigated the impact of IL-10 in COVID-19, through the ex-vivo assessment of the effects of exogenous IL-10 on SARS-CoV-2-specific-response using a whole-blood platform. Methods: Two cohorts were evaluated: in “study population A”, plasma levels of 27 immune factors were measured by a multiplex (Luminex) assay in 39 hospitalized “COVID-19 patients” and 29 “NO COVID-19 controls” all unvaccinated. In “study population B”, 29 COVID-19 patients and 30 NO COVID-19-Vaccinated Controls (NO COVID-19-VCs) were prospectively enrolled for the IL-10 study. Whole-blood was stimulated overnight with SARS-COV-2 antigens and then treated with IL-10. Plasma was collected and used for ELISA and multiplex assay. In parallel, whole-blood was stimulated and used for flow cytometry analysis. Results: Baseline levels of several immune factors, including IL-10, were significantly elevated in COVID-19 patients compared with NO COVID-19 subjects in “study population A”. Among them, IL-2, FGF, IFN-γ, and MCP-1 reached their highest levels within the second week of infection and then decreased. To note that, MCP-1 levels remained significantly elevated compared with controls. IL-10, GM-CSF, and IL-6 increased later and showed an increasing trend over time. Moreover, exogenous addition of IL-10 significantly downregulated IFN-γ response and several other immune factors in both COVID-19 patients and NO COVID-19-VCs evaluated by ELISA and a multiplex analysis (Luminex) in “study population B”. Importantly, IL-10 did not affect cell survival, but decreased the frequencies of T-cells producing IFN-γ, TNF-α, and IL-2 (p<0.05) and down-modulated HLA-DR expression on CD8+ and NK cells. Conclusion: This study provides important insights into immune modulating effects of IL-10 in COVID-19 and may provide valuable information regarding the further in vivo investigations.